A framework to facilitate development and testing of image‐based river velocimetry algorithms - Legleiter, Carl J.; Kinzel, Paul J. (Earth surface processes and landforms, 2024)
Image‐based methods have compelling, demonstrated potential for characterizing flow fields in rivers, but algorithms like particle image velocimetry (PIV) must be further tested and improved to enable more effective use of these techniques. This paper presents a framework designed for this exact purpose: Simulating Hydraulics and Images for Velocimetry Evaluation and Refinement (SHIVER). The approach involves coupling a hydrodynamic model with a synthetic particle generator to advect particles between frames, as dictated by local velocity vectors and thus construct a plausible image sequence specific to the reach of interest. The resulting time series can then be used as input to a velocimetry algorithm to compare image‐derived estimates with known (modelled) velocities to perform an exhaustive, spatially distributed accuracy assessment. As an example application of SHIVER, we examined the effects of interrogation area (IA) size, frame rate, flow velocity, and image sequence duration on the performance of a standard PIV algorithm. This analysis indicated that image‐derived velocities were generally in close agreement with those from the flow model (root mean square error <10% and mean bias <3%), except when small IAs were coupled with low frame rates. Velocity estimates were most accurate for the lowest modelled discharge ( R2=0.97 at baseflow) and became less reliable as the mean flow velocity increased ( R2=0.92 for an intermediate discharge and R2=0.86 at bankfull). Accuracy was essentially independent of image sequence duration, implying that long occupations might not be necessary. Errors were concentrated along channel margins, where PIV‐based velocities tended to be greater than those from the flow model. Small IAs led to underpredictions of velocity, while larger IAs led to overpredictions. SHIVER is highly modular and could be updated to make use of different hydrodynamic models or image simulators. The framework could also facilitate more thorough sensitivity analyses and comparison of various velocimetry algorithms. The Simulating Hydraulics and Images for Velocimetry Evaluation and Refinement (SHIVER) framework facilitates testing of image‐based river velocimetry algorithms and can foster their improvement. The approach involves coupling a hydrodynamic model with a synthetic particle generator to advect particles between frames, as directed by the local velocity field, and thus construct an image sequence specific to the reach of interest. Using this time series as input to a velocimetry algorithm enables exhaustive accuracy assessment via comparison to the modelled flow field.